The Mediating Role of Employee Happiness in Digital Technology Adoption and its Impact on Performance and Work Culture in Coal Mining XYZ Company - Sigit Herutomo; Henndy Ginting (PT. Publikasiku Academic Solution, 2025)
Grounded in four interconnected constructs (employee happiness, digital technology adoption, employee performance, and work culture), this study examines how psychological factors influence technology adoption in high-risk, labor-intensive industries like coal mining. Addressing a gap in literature, it explores how digital tools affect employee performance amidst physical demands and job stress. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data from 124 frontline employees at PT XYZ, four hypotheses were tested: (1) digital technology adoption positively impacts employee happiness; (2) happiness mediates the relationship between digital technology and performance; (3) happiness mediates the relationship between digital technology and work culture; and (4) work culture moderates the happiness-performance link. Results show digital tools significantly boost employee happiness (B = 0.612, p < 0.001), which improves performance (B = 0.317, p = 0.001) and fosters a positive work culture (B = 0.491, p < 0.001). The moderating effect of work culture was not significant (B = 0.102, p = 0.212), indicating cultural rigidity in traditional industrial settings. This research extends models like the Technology Acceptance Model (TAM) by integrating emotional outcomes, demonstrating that digital tools reduce stress and enhance motivation beyond efficiency. Practically, it recommends three interventions: a Digital-Engagement Dashboard, cross-functional Innovation Labs, and leadership training to build digital empathy. These align technology with employee well-being. Future research should validate this framework across industries and time. By positioning happiness as a mediator, the study offers insights bridging organizational psychology and digital transformation in high-risk sectors.